Physical properties of Paraserianthes falcataria / Suria Mohamad Akhir and Jamaludin Kasim - Mohamad Akhir, Suria; Kasim, Jamaludin (2011)
The study was conducted with the objective to determine basic properties and effects of distance from pith on potential species for the establishment of short-rotation forest plantation in Malaysia. For this purpose, three 8-year-old Paraserianthes falcataria were studied to obtain its specific gravity against 13 year-old Paraserianthes falcataria from previous studies and also to determine moisture content of this tree. Results show significant differences in specific gravity from the three sample trees where there is an increase of specific gravity from near pith to near bark. The specific gravity of P falcataria was also observed to decrease from bottom to top whitr the mpisture content increase with tree portion. While the green moisture content of Paraserianthes falcataria decreases from near pith to near bark.